Air pollution assessment on particulate matter dispersion at mega construction site - Ramli, Azizan; Sulaiman, Siti Zubaidah; Azoddein, Abdul Aziz Mohd; Mohd Armi, Abu Samah; Mimi Haryani, Hassim (2019)
Deterioration of air quality is becoming an issue in the global environment, especially in Malaysia. The increase of the particulate matter’s generative industry such as construction, biomass energy plant and foods producers in Malaysia due to the growth of population, and rapid urbanization are the main factors of contribution to the highest industrial air pollution sources by the state from the year 2010 to 2015. One of the pollutants involved in the cause of air pollution especially in Malaysia is from particulate matter emission. The emission of particulate matter in Malaysia comes from three primary sources which are mobile, stationary, and open burning sources. In the year 2000 - 2015, the estimation percentage of annual particulate matter emission accumulated in Malaysia is 7% for every year of air pollution sources. Consequently, this distribution of particulate matter in the atmosphere produced by human activities can cause serious problem such as radiation balance of the Earth, change in the cloud formation, contribution to global warming, reduced visibility and to be worst affected to the human health especially to the workers and publics. Based on the result of the calculated data from the selected site, the average concentration of particulate emitted to the air in 24-hour mean is 0.6944 mg/m3 for both sizes. The average concentration of particulate matter is then compared with the guidelines provided by the World Health Organization (WHO). From the values, the concentration of both PM2.5 and PM10 are exceeding the level of 24 hour mean of emission and can be concluded as critical.